2001
DOI: 10.1159/000056998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative architectural aspects of regions of conserved synteny on human chromosome 11p15.3 and mouse chromosome 7 (including genes WEE1 and LMO1)

Abstract: Human chromosome 11p15.3 is associated with chromosome aberrations in the Beckwith Wiedemann Syndrome and implicated in the pathogenesis of different tumor types including lung cancer and leukemias. To date, only single tumor-relevant genes with linkage to this region (e.g. LMO1) have been found suggesting that this region may harbor additional potential disease associated genes. Although this genomic area has been studied for years, the exact order of genes/chromosome markers between D11S572 and the WEE1 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…45 % (both human and mouse) in the major part of the region under study. A similar, but shorter AT-rich subregion has been detected in the adjacent contig containing genes LMO1/TUBBY (Cichutek et al, 2001). Earlier studies using density gradient centrifugation have shown that DNA of mammalian genomes indeed can be separated into classes of distinct GC content.…”
Section: Global Comparison Of the Human And The Mouse Sequencesupporting
confidence: 54%
See 2 more Smart Citations
“…45 % (both human and mouse) in the major part of the region under study. A similar, but shorter AT-rich subregion has been detected in the adjacent contig containing genes LMO1/TUBBY (Cichutek et al, 2001). Earlier studies using density gradient centrifugation have shown that DNA of mammalian genomes indeed can be separated into classes of distinct GC content.…”
Section: Global Comparison Of the Human And The Mouse Sequencesupporting
confidence: 54%
“…We therefore isolated a contiguous set of genomic clones from both human and mouse (ca. 1.6 and 1.4 Mb, respectively), which provided the basis for accurately determining the nucleotide sequence of almost the entire region (Cichutek et al, 2001; and this paper). Here we present the large-scale comparative genomic analysis of roughly 730 kb of human and 620 kb of mouse sequence, centered around the ST5 gene.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Serine/threonine kinase 33 ( stk33 ) was first discovered in the course of comparative genome analyses of human chromosome 11p15.3 and its orthologous region in the mouse [ 1 3 ]. This region is highly syntenic (see Additional file 1 : Figure S1) and known to be associated with several diseases including different types of cancer [ 4 8 ].…”
Section: Introductionmentioning
confidence: 99%